Drawing the Line on Legislative Privilege: Interpreting State Speech or Debate Clauses in Redistricting Litigation - J. Pierce Lamberson (Washington University Law Review, 2017)
The United States Constitution and forty-three state constitutions include a Speech or Debate Clause granting legislators a legal privilege for their legislative work.1 Although there is a well-developed body of federal Speech or Debate Clause law granting an absolute privilege to legislators, case law interpreting many state Speech or Debate Clauses is undeveloped.2 One context in which state Speech or Debate Clauses are tested is redistricting litigation.3 State courts provide a desirable forum for challengers seeking to expose partisan gerrymandering in redistricting plans.4 Because the potential for exposing partisan gerrymandering increases if state legislators’ statements and legislative documents are accessible, many observers have concluded that Speech or Debate Clause protections should be watered down in the redistricting context.5 However, failing to strongly enforce state Speech or Debate Clause protections would lead to negative effects for representative democracy.6 Rather than weaken Speech or Debate Clause protections, a better solution is to restrict the free reign of partisan legislators over the redistricting process by using independent commissions. Part I of this Note traces the history and development of the federal Speech or Debate Clause and legislative privilege with an emphasis on Supreme Court case law. Part II summarizes major trends in state court interpretation of state Speech or Debate Clause cases. Part III examines state Speech or Debate Clause treatment in the context of redistricting litigation and surveys relevant state supreme court cases. Finally, Part IV proposes a framework for approaching state Speech or Debate Clauses in state redistricting litigation and explores the feasibility of independent redistricting commissions as a solution to redistricting problems.
Keywords: United States Constitution; Speech or Debate Clause; redistricting; legislative privilege; Articles of Confederation; Killbourn v. Thompson; 103 U.S. 168 (1881)